KETERLIBATAN ANAK DALAM TINDAK PIDANA DITINJAU DARI PERSPEKTIF HUKUM PIDANA ANAK DI INDONESIA - Wahyulina, Diah; Chrisdanty, Febry (Jurnal Magister Hukum Perspektif, 2023)
Children are the next generation of the nation so they need maximum coaching, guidance and protection so that the child will not commit an act that violates the law. The involvement of children, who in this case are perpetrators of a criminal Children are the next generation of the nation so they need maximum coaching, guidance and protection so that the child will not commit an act that violates the law. The involvement of children, who in this case are perpetrators of a criminal act, must be given the rights and protection of children as vulnerable legal subjects as regulated in the applicable laws and regulations. Through a normative legal approach, this research analyzes legal regulations that regulate the rights and protection of children involved in criminal contexts. The aims of this research are firstly to find out the meaning of children in Indonesian laws and regulations, secondly to find the concept of children's criminal law legislation in Indonesia which regulates children's involvement in criminal acts according to a normative approach, and thirdly to find out the procedures for handling cases of involvement. children in juvenile crimes from the perspective of juvenile criminal law in Indonesia through the principles of child human rights and the principles of the best interests of the child. The results of this research are that the handling of cases of child involvement in juvenile crimes from the perspective of juvenile criminal law in Indonesia is by placing more emphasis on the principles of children's human rights and the best principles for the interests of children because although there has been progress, challenges remain, and improvements Continuous harmonization of policies, consistent implementation, and strengthening the rehabilitation system can optimize the protection and development of children involved in the context of juvenile criminal justice. Keywords: Child Involvement, Child Crime, Child Criminal Law